Studi In Silico Jatropon, Jatropolon A, Jatropolon B, dan Turunan Sebagai Anti Kanker Terhadap Reseptor Bcl-2 - Syaifullah, Ramanda R; Sholeh, Muhammad; Azizah, Wafiq; Kasman, Nur F; Nursamsiar; Paluseri, Andi; Lukman (Sam Ratulangi University, 2025)
Jatrophone and its congeners jatropholone A and B, have shown potent cytotoxicity by triggering apoptosis through Bcl-2–regulated mechanisms. We evaluated jatrophone, jatropholones A and B and twenty-two related derivatives as Bcl-2–targeting anticancer leads using in silico approaches. Molecular properties and preliminary affinity estimates were obtained with ChemOffice; molecular docking to the Bcl-2 binding site was performed with AutoDock Tools. ADME predictions used PreADMET and toxicity risk assessment applied Toxtree with the Benigni/Bossa rule-base. Twelve compounds violated Lipinski’s rule of five, while thirteen displayed identical amino-acid contacts at the receptor, suggesting a conserved binding mode. Predicted plasma protein binding was high for most derivatives except compounds 20 and 22. Six derivatives were flagged as potentially genotoxic; none were predicted mutagenic. Docking ranked jatropholone A as the top candidate (binding energy −8.67 kcal/mol). These results prioritize jatropholone A for experimental validation as a promising Bcl-2–targeting anticancer agent.